PROSES TERMAL NASI RENDANG KALENG: EVALUASI MIKROBIOLOGI, KIMIA DAN ORGANOLEPTIK - , DANIEL, Prof. Dr. Ir. Mary Astuti, MS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A research of sterilization time trial on canning rice with beef rendang had been conducted. The severe heat of thermal processing killed all the microbes and a hermetically sealed container prevented microbes from entering the can and deteriorated the content. Edible vegetable oil was added to the cooked rice subjected to the canning to prevent each grain from sticking. Thermal treatments were given at temperature and different time combination of 121 0C for 10, 20 and 30 minutes respectively in order to interpret the effect on the microbiological, chemical and sensory profile of canned rice with rendang. The stability of samples was evaluated at the interval of 10 days from the initial day of canning until the 50 days of incubation. The cooked rice with addition of edible vegetable oil (palm oil or coconut oil or soybean oil) showed the good acceptance on the aroma, texture, flavor, and overall attribute. The hedonic test indicated the sensory stability of canned rice with rendang, showing no significant decline on the aroma, appearance and texture attribute even after 50 days period of storage. Storage time affected on significant increase of free fatty acid profile especially on higher incubation temperature. The protein solubility was decreasing at the initial period of storage and then showed a slight increase until the end of incubation period. The shelf life prediction was carried out based on the acceleration shelf life testing. Samples on longer duration of sterilization (20 and 30 minutes) had lower counts of microbes than the shorter duration (10 minutes) during 50 days period under 40, 50, dan 60 0C of incubation temperature, indicated the good microbial quality of samples evaluated (total plate count is less than 104 colony forming unit per gram). Canned rice with rendang had shelf life of 23.25 months, 40.20 months, dan 39.47 months when sterilized for 10, 20 and 30 minutes, respectively. One portion of canned rice with rendang provided approximately 360 kcal.